Analysis of Strong Ground Motion Characteristics for the Jishishan MS6.2 Earthquake December 18, 2023 - Duan Xueliang; Liu Yanqiong; Zhou Zhenghua; Bian Zhu; Han Yi; He Jiacong; Peng Chen; Zhang Long (Shock and Vibration)
The MS6.2 earthquake occurred in Jishishan, Gansu Province, China, on December 18, 2023. Based on some strong seismic acceleration time histories captured by some stations of China National Strong Earthquake Observation Network and National Earthquake Early Warning Network, the spatial distribution characteristics, rupture directivity effect, hanging wall and footwall effect, response spectrum characteristics, and attenuation of the peak ground acceleration (PGA) were analyzed in this paper. It can be used as reference for the site determination of post-earthquake reconstruction and seismic design of engineering structures. The analysis shows that the spatial distribution of strong ground motion of the Jishishan MS6.2 earthquake is mainly controlled by the distribution of causative fault. Near the fault, the effect of rupture directivity is obvious. The effect of hanging wall and footwall significantly affects the distribution of PGAs for this earthquake, causing a pronounced asymmetric pattern about PGAs relative to the fault, with slower attenuation on the hanging wall compared to the footwall. The type of site obviously affects the characteristics of response spectrum. The ground motion intensity observed at the epicenter of this earthquake significantly exceeded the levels of rare and extremely rare seismic events in the current seismic design codes. The attenuation relationship of PGA obtained by regression analysis shows that ones in the 5th generation Chinese ground motion parameter zoning map for the Qinghai-Tibet region underestimate the horizontal PGA.